An Updated Review of Various Medicinal Applications of p-Co umaric Acid: From Antioxidative and Anti-Inflammatory Properties to Effects on Cell Cycle and Proliferation - Abazari, Mohammad F.; Nasiri, Navid; Karizi, Shohreh Zare; Nejati, Fatemeh; Haghi-Aminjan, Hamed; Norouzi, Sara; Piri, Peyman; Estakhr, Leila; Faradonbeh, Davood Rabiei; Kohandani, Mina; Daliri, Karim; Sanadgol, Nima; et al. (Mini Reviews in Medicinal Chemistry, 2021)
P-Coumaric acid (p-CA) is a hydroxycinnamic acid, an organic compound that is a hydroxyl derivative of cinnamic acid. P-CA is the most abundant isomer in nature and can be found in a wide variety of edible plants such as fungi, peanuts, navy beans, tomatoes, carrots, basil, and garlic. Recently, the therapeutic properties of p-CA have received a great deal of attention from scientific society. Here, we described the medicinal effects of p-CA on various pathological conditions. This review was performed via evaluating PubMed reported studies from January 2010 to January 2020. Also, reference lists were checked to find additional studies. All intermediation or complementarity of animal models, case-control and cohort studies, in vitro studies, and controlled trials (CTs) on p-CA were acceptable. However plant extract studies without indication of main active substances were excluded due to the considerable diversities and heterogeneities. According to recent evidence regarding the beneficial effects of p-CA, numerous diseases such as nephropathies, cardiovascular diseases, neuroinflammatory diseases, liver diseases, cancers, and some metabolic disorders could potentially be controlled by this natural herb. Interestingly, autophagy is a novel molecular mechanism involved in the crosstalk between classic effects of p-CA and introduces alternative therapeutic pathways for this compound. Much work remains in clarifying the main therapeutic properties among the various p-CA effects; these will be the subject of forthcoming work, resulting in presenting further mechanism of action.
Keywords: Apoptosis